Implementation of business strategy using the Balanced Scorecard technique on the example of RaiseBerry Company - Golińska, Sylwia (My University, 2011)
The main aspect of this study is the process of strategy implementation. Its significance was widely presented by means of the Balanced Scorecard methodology. In this thesis the project of the card for RaiseBerry Company is described and widely explained. First three sections relate to general process of strategy accomplishment placing greater emphasis on the implementation stage which is the subject of present elaboration. The developed Balanced Scorecard tool is composed of 13 major objectives which lead to strategy realization. They are grouped into four mutually correlative perspectives: financial, customer, processes and learning & growth. In the final subsection are presented all recommendations and conclusions with reference to considered issues.

Głównym przedmiotem zainteresowania niniejszej pracy magisterskiej jest proces wdrażania strategii w przedsiębiorstwie. Jej istota oraz sposób implementacji zostały przedstawione za pomocą metody, jaką jest Strategiczna Karta Wyników. W pracy został zawarty oraz szeroko wyjaśniony projekt karty dla firmy RaiseBerry. Pierwsze trzy rozdziały opisują proces realizacji strategii w przedsiębiorstwie. Największy nacisk został położony na etap wdrażania strategii, który jest również głównym obiektem rozważań tegoż opracowania. Wypracowana Strategiczna Karta wyników składa się z 13 mierników, które mają za zadanie doprowadzić przedsiębiorstwo do realizacji wybranej strategii. Zostały pogrupowane w 4 wzajemnie oddziałujące perspektywy: finansową, klienta, procesów oraz rozwoju. W ostatnim podrozdziale zawierają się wszystkie rekomendacje oraz sugestie, co do wdrażania omawianego narzędzia w firmie.
Wdrażanie strategii za pomocą Strategicznej Karty Wyników na przykładzie firmy RaiseBerry
Keywords: strategy; strategic management; strategy implementation; Balanced Scorecard; strategy accomplishment; objectives; key performance indicators; strategia; zarządzanie strategiczne; wdrażanie strategii; Strategiczna Karta Wyników; realizacja strategii; cele; kluczowe czynniki sukcesu